Pharmacophore Modeling, Molecular Docking, and ADMET Approach for Identification of Anti-Cancer Agents Targeting the C-Jun N-Terminal Kinase (JNK) Protein - Nur Ayu Ramadanti; Linda Erlina; Rafika Indah Paramita; Aryo Tedjo; Fadillah Fadillah; Surya Dwira (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
One of the most prevalent cancers in Indonesia is breast cancer, based on Indonesia's pathological-based registration. Breast cancer is a complex, heterogeneous disease classified into hormone-receptor-positive, human epidermal growth factor receptor-2 overexpressing (HER2+) and triple-negative breast cancer (TNBC) based on histological features. Patients with HR+, HER2- Early Breast Cancer (EBC) do not experience recurrence or recurrence for a long time with currently available standard therapy [11]. However, up to 30% of patients with high-risk clinical and/or pathological features may experience a relapse in the first few years. This results in the need for research and development regarding updates in medicine both in terms of treatment and targets and drug compounds used. The c-Jun N-terminal kinase (JNK) protein functions in signaling and influences the apoptotic pathway as well as cancer cell survival. In this study, an insilico screening experiment of inhibitory compounds was carried out on the JNK protein receptor target by screening compounds and molecular docking of compounds for breast cancer therapy.Two novel herbal compounds, Mangostin and ent-Copalyl Dyphospate, have the potential to be turned into medicines that may cause apoptosis through JNK protein targets according to an in-silico-based molecular simulation technique